Religious education and training in developing future human resource professionals: views from experts and teachers - Rahim M. Sail; Khadijah Alavi; Lukman Abdul Mutalib; Anwar Ahmad; Shamsul Shah Tarjo; Nor Ellina Abdul Razak (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2013)
The main purpose of this study was to explore the views of Islamic religious experts and excellent Islamic teachers on the development of future human resource professionals. A qualitative design was employed to explore themes of this study among Islamic experts and excellent Islamic teachers. Participants of the study comprised 8 Islamic religious experts and 12 excellent Islamic teachers. In-depth interviews with the participants were conducted to gather the data. The findings indicated that Islamic religious experts and excellent Islamic teachers viewed, the process and practices of human resource development (HRD) would be greatly strengthened through understanding and application of the contents of the al-Quran and Hadiths. It would be able to apply and practice Islamic concepts and ethics in carrying out HRD functions. Implications that can be drawn from the findings suggest that religious concepts and ethics should be integrated or infused in the pre-service curriculum to prepare for a “balanced” HRD professional. On the other hand, in-service training programs for HRD professionals should also include religious concepts and ethics to fortify them with the foundations of integrity, professionalism and accountability.